Immunologic phenotype of patients with long-COVID syndrome of 1-year duration - García-Abellán, Javier; Fernández, Marta; Padilla, Sergio; García, José Alberto; Agulló, Vanesa; Lozano, Valle; Ena, Nuria; García-Sánchez, Lidia; Gutiérrez, Félix; Masiá, Mar (Frontiers in Immunology, 2022)
Background: The pathophysiology of long-COVID remains unknown, and information is particularly limited for symptoms of very long duration. We aimed to assess the serological, T-cell immune responses and ANA titers of patients with long-COVID-19 syndrome of 1-year duration. Methods: Prospective, longitudinal study of hospitalized COVID-19 patients followed-up for 12 months. Sequential blood samples and COVID-19 symptom questionnaires (CSQ) were obtained, and humoral and cellular immune responses, antinuclear antibodies (ANA) and inflammation biomarkers were analyzed. Results: Of 154 patients discharged from hospital, 72 non-vaccinated with available CSQ in all visits were included. Of them, 14 (19.4%) reported persistent symptoms both at 6-months and 12-months, mainly asthenia (15.3%), myalgia (13.9%), and difficulty concentrating/memory loss (13.9%). Symptomatic patients were more frequently women, smokers, showed higher WHO severity score, and a trend to higher ICU admission. In the adjusted analysis, long-COVID syndrome was associated with lower frequency of detectable neutralizing antibodies (adjusted hazard ratio [aHR] 0.98; 95% confidence interval [CI], 0.97-0.99) and lower SARS-CoV-2-S1/S2 titers (aHR [95%CI] 0.14 [0.03–0.65]). T-cell immune response measured with a SARS-CoV-2-interferon-γ release assay was not different between groups. There was a higher frequency of positive ANA titers (≥160) in symptomatic patients (57.1% vs 29.3%, p=0.04), that was attenuated after adjustment (aHR [95%CI] 1.01 [1-1.02]). Levels of C-reactive protein and D-dimer were higher during follow-up in symptomatic patients, but with no differences at 12 months. Conclusion: Patients with 1-year duration long-COVID-19 syndrome exhibit a distinct immunologic phenotype that includes a poorer SARS-CoV-2 antibody response, low-degree chronic inflammation that tends to mitigate, and autoimmunity.